Passer les frontières dans la Corne de l’Afrique : trois logiques de survie autour des figures du réfugié, du passeur et du rebelle - Alexandre Lauret (EchoGéo)
The Horn of Africa and Yemen represent an area subject to numerous political crises and territorial disputes. The present article aims to comprehend how the crises foster new places of exchange between three different types of stakeholders: the Yemenite refugee fleeing war, the smuggler routing Ethiopian migrants, and the Afar rebel fighting the Djiboutian government. Each of them gives a specific example of a strategy for survival: crossing the border for exile, economic opportunity, and the support of an armed rebellion from abroad. Those three strategies invite reflection on how populations react to deal with local political hazards in the countries of Yemen and the Horn of Africa.